Non-formal institutions, informal economies, and the politics of inclusion - Aili Mari Tripp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Africa's formal economies responded poorly to economic reform measures in the 1980s and 1990s while informal markets and institutions responded dynamically and proved to be more resilient. Using comparative analysis of African informal economies, this study explains why this was the case. It outlines the economic rationales that drive these informal economies to show how their logic often derives from social considerations that may be at odds with the goals of profit maximization. It then maps out some of the institutional terrain within which the informal sector operates. The study also analyzes the extent to which government policies in Africa have facilitated and constrained the informal sector; it describes continuing impediments to the growth of local and informal markets; and explores incentives that would enhance informal institutions.
Keywords: O17; O55; P46; Z13; P11; G2; 330; informal economy; non-formal institutions; structural adjustment; economic policy; Schattenwirtschaft; Wirtschaftliche Anpassung; Afrika